Thermally conductive composition
A composition of diamond, alumina, aluminum nitride, boron nitride, and zinc oxide fillers with silicone polymers enhances thermal conductivity and stability, addressing the limitations of conventional TIMs in advanced electronic devices.
Patent Information
- Application Number
- JP2024013139
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-12-04
- Filing Date
- 2024-01-31
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-01-31
AI Technical Summary
Conventional thermal interface materials (TIMs) fail to achieve high thermal conductivity (>10 W/mK) while maintaining low pump-out, low bleed-out, cracking, and hardness increase, and reliability during cold-hot cycling/shock, which are critical for advanced electronic devices.
A composition comprising a mixture of diamond, alumina, aluminum nitride, boron nitride, silicon carbide, and zinc oxide fillers, combined with silicone polymers and resins, optimized for high thermal conductivity (>12 W/mK) and stability during thermal cycling.
The composition maintains high thermal conductivity, low hardness, and stability under extreme temperature variations, ensuring reliable thermal management for electronic devices.
Smart Images

Figure 2025000539000022 
Figure 2025000539000001 
Figure 2025000539000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition comprising an organopolysiloxane and a first thermal conductivity enhancer, a second thermal conductivity enhancer, and optionally a third thermal conductivity enhancer. [Background technology]
[0002] With the development of electronic devices toward miniaturization and high-density integration, the heat generated by electronic devices gradually increases, and thermal failure becomes a major problem that impedes the performance, reliability and lifespan of electronic devices. Therefore, efficient thermal management is crucial to solve this problem. To improve the heat removal for electronic devices, thermal interface materials (TIM) are widely used between two solid contact surfaces of a heat source and a heat sink. These materials come in various forms, such as grease, gap filler, pre-cured gel, hardenable material (one-component or two-component), phase change material, elastomeric pad, adhesive, thermal tape, metal alloy and solder, etc. The gap between the two solid surfaces (chip and heat sink) is non-uniform and otherwise filled with air, which has low thermal conductivity. The gap is filled with thermal interface material to provide a thermal conduction path. If desired, multiple thermal interface materials may be used between different solid surfaces to provide a continuous conduction path for heat removal.
[0003] The advent of 5G communication technology in the telecommunications domain and the Internet of Things (IoT) in the consumer and industrial domains will further increase the performance requirements for TIMs. 5G and IoT devices (using 5G) will operate at higher frequencies, higher device density, higher bandwidth, lower latency, small feature sizes and lower power, along with the demands for much higher reliability and availability. These factors have made the heat removal requirements for electronic devices much more stringent, and a move from low thermal conductivity of 3 to 5 W / mK to TIMs with an average of 6 to 10 W / mK is a general trend in the industry, and has prompted the development of even higher thermal conductivity beyond 10 W / mK. The development of next-generation integrated circuits (ICs), three-dimensional (3D) integration and ultra-high speed and high power density communication devices is making the requirements for thermal management extremely stringent.
[0004] Conventional TIMs filled with thermally conductive particles require a high volume fraction v (>50%) of fillers such as alumina and ZnO to achieve a composite thermal conductivity (TC) in the range of 1 to 5 W / mK. Many products also utilize metallic fillers such as aluminum when the electrical conductivity requirement is relaxed. However, additional fillers such as BN fillers, AlN fillers, diamond fillers, SiC fillers, and combinations thereof have been disclosed in many patent applications to achieve high TC (>10 W / mK). The advantage of these fillers is that they are electrically insulating and have much higher thermal conductivity (high TC fillers). Besides thermal conductivity, TIM formulations must exhibit various other important properties for use in applications. These may include low thermal resistance, low volatility, low pump-out, low bleed-out, low cracking, thermal stability, hardness, high output for application at a given viscosity, shear rate, pump pressure, etc. Stability of properties during low-high temperature cycling / impact should also be demonstrated by running tests for up to 1000 to 2000 hours. These properties are achieved by careful design of the TIM formulation, combining the appropriate polymer-resin-dispersant combination with high filler loading in the composition, as disclosed below.
[0005] Japanese Patent No. 7007161 describes a composition containing a diamond filler, in which the shape of the diamond filler is granular (non-spherical, more preferably polyhedral, more preferably hexahedral, octahedral, etc., particularly preferably hexahedral), has 10 to 18 faces, and has a sphericity of more than 0.2. The size of the diamond is 0.01 to 100 μm. The difference between the true specific gravity of the diamond and the true specific gravity of the thermal conductivity improver is 0.2 to 4 g / cm. 3The ratio of the volume average particle size of the thermal conductivity enhancer to the volume average particle size of the diamond is 0.01 to 0.5. The overall thermal conductivity shown is low, <10 W / mK. Japanese Patent No. 7084143 describes a heat dissipation composition, a heat dissipation member, and a filler aggregate for a heat dissipation member. The composition contains diamond (greater than 15 volume % diamond) along with a plurality of fillers exhibiting a thermal conductivity greater than 10 W. Also mentioned is a total void volume (<3%), a contact angle (<70°) of the polymer matrix to the thermally conductive filler containing diamond particles, and the diamond particles have a surface oxygen content (>5%). Japanese Patent No. 2938428 describes a heat reducing grease containing liquid silicone in combination with diamond and a thermally conductive inorganic filler such as AlN, having a consistency ranging from 280 to 350 and a thermal conductivity ranging from 2.5 to 4 W / mK. China Patent No. 112226199 describes an insulating composition of ultra-high thermal conductivity curable paste, which contains thermally conductive fillers such as diamond and functional fillers such as ferric oxide, and has a thermal conductivity of 11.8 W / mK and a throughput of 33 g per minute.
[0006] However, these proposed solutions do not address the need for thermally conductive compositions having a desired combination of attributes through the use of a combination of thermally conductive fillers. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides a composition comprising a mixture of a polymer and a thermally conductive filler, the loading of which in the composition provides a composition with high thermal conductivity while maintaining good dispensability and meeting all other relevant CTQs (critical to quality characteristics), such as low pump-out, low bleed-out, cracking, low hardness increase and reliability during low-temperature-high-temperature cycles / shocks (-40°C to 150°C) for 500 to 1000 hours. The present invention incorporates diamond as the primary filler in a thermally conductive composition. It is shown herein that diamond combined with alumina, AlN, BN, SiC and ZnO fillers form an ideal combination to achieve thermal conductivity of over 12 W / mK with stable dispensing volume and outstanding thermal stability in conjunction with silicone polymers and resins. All of these compositions are electrically non-conductive.
[0008] The following presents a summary of the disclosure to provide a basic understanding of some aspects of the invention. This summary is not intended to identify key or critical elements, nor is it intended to define any limitations to the embodiments or claims. Moreover, this summary may provide a simplified overview of some aspects that may be described in more detail in other parts of the disclosure. [Means for solving the problem]
[0009] In one embodiment, provided is a method for producing a medicament for the treatment of a cancer, comprising: (A) an organopolysiloxane, (i) an alkenyl-functionalized diorganopolysiloxane of formula (Ia) M 1 a M 2 b D 1 c D 2 d T 1 e T 2 f Q g (Ia) [In the formula, M 1 =R 1 R 2 R 3 SiO 1 / 2 M 2 =R 4 R 5 R 6 SiO 1 / 2 D 1 =R 7 R 8 SiO 2 / 2 D 2 =R 9 R 10 SiO 2 / 2 T 1 =R 11 SiO 3 / 2 T 2 =R 12 SiO 3 / 2 Q = SiO 4 / 2 where R 2 , R 3 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 12 are each independently selected from monovalent aliphatic, aromatic and fluorohydrocarbon groups or alkoxy groups having from 1 to 60 carbon atoms; R 1 , R 7 , R 11 are each independently selected from monovalent aliphatic, aromatic or fluorohydrocarbon radicals having from 1 to 60 carbon atoms and containing at least one terminal olefinic bond; The subscripts a, b, c, d, e, f, and g are 0 or positive integers, subject to the restrictions that 1≦a+b+c+d+e+f+g≦6000 and a+c+e≧1. and (ii) a hydrogen-functionalized organopolysiloxane of formula (Ib) M 1 a′ M 2b′ D 1 c′ D 2 d′ T 1 e′ T 2 f′ Q g′ (1b) [In the formula, M 1 =R 13 R 14 R 15 SiO 1 / 2 M 2 =R 16 R 17 R 18 SiO 1 / 2 D 1 =R 19 R 20 SiO 2 / 2 D 2 =R 21 R 22 SiO 2 / 2 T 1 =R 23 SiO 3 / 2 T 2 =R 24 SiO 3 / 2 Q = SiO 4 / 2 where R 14 , R 15 , R 16 , R 17 , R 18 , R 20 , R 21 , R 22 , R 24 is a monovalent aliphatic, aromatic or fluorohydrocarbon radical having 1 to 60 carbon atoms; R 13 , R 19 , R 23 is hydrogen, The subscripts a′, b′, c′, d′, e′, f′, and g′ are zero or positive integers, subject to the restrictions that 1≦a′+b′+c′+d′+e′+f′+g′≦6000 and a′+c′+e′≧1. However, when a′+c′+e′=1, a+c+e>1, and when a+c+e=1, a′+c′+e′>1 are also included. or an organopolysiloxane comprising a crosslinked product of (i) and (ii); (B) a composition is provided that includes a first thermal conductivity enhancer having a particle size in the range of 60 to about 200 μm, a second thermal conductivity enhancer having a particle size in the range of 0.5 to about 30 μm, and a third thermal conductivity enhancer having a particle size in the range of 0.01 to less than 0.5 μm. As used herein, "particle size" refers to the volume average particle size unless the context indicates otherwise.
[0010] In one embodiment, the composition comprises a dispersant represented by formula (II): [ka] [In the formula, R 25 is a group having an alkoxysilyl group having 1 to 4 carbon atoms, R 26 is a linear organosiloxy group (III), [ka] [In the formula, each R 28 are independently monovalent hydrocarbon radicals having 1 to 12 carbon atoms, L is selected from monovalent hydrocarbon radicals having 1 to 6 carbon atoms and alkoxysilyl radicals having 1 to 4 carbon atoms, and k is an integer from 10 to 500. Each X is independently a divalent hydrocarbon group having from 2 to 10 carbon atoms; each of h and i is independently an integer of 1 or greater; j is an integer equal to or greater than 0, h+i+j is an integer equal to or greater than 4, Each R 27 are independently selected from hydrogen and monovalent hydrocarbon radicals having 1 to 6 carbon atoms; or [ka] [In the formula, R 29 represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group, and each R 30 each independently represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group; R 31 and R 32 each represents the same or different unsubstituted or substituted monovalent hydrocarbon group, and each R 33 each independently represents a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group; 34 each independently represents an unsubstituted or substituted alkyl group, alkoxyalkyl group, alkenyl group, or acyl group, and n represents an integer of 2 to 20. The dispersant includes a dispersant represented by:
[0011] In another embodiment, the dispersant comprises two or more hydrolyzable organopolysiloxane compounds of formula (II).
[0012] In yet another embodiment, the dispersant comprises a first hydrolyzable organopolysiloxane represented by formula (II) and having a value of k ranging from 10 to 50, and a second hydrolyzable organopolysiloxane represented by formula (II) and having a value of k ranging from 100 to 500.
[0013] In one embodiment, the organopolysiloxane has an H / Vi ratio greater than 0.4.
[0014] In yet another embodiment, the composition comprises a first thermal conductivity enhancer in an amount of about 15 wt% to about 50 wt%, based on the total weight of the composition. The first thermal conductivity enhancer has an average particle size in the range of 60 to about 200 μm, preferably 100 to 170 μm.
[0015] In another embodiment, the first thermal conductivity enhancer is diamond.
[0016] In another embodiment, the diamond has a surface oxygen content of greater than 10%.
[0017] In another embodiment, the composition comprises a second thermal conductivity enhancer in an amount from about 20 wt % to about 50 wt %, based on the total weight of the composition.
[0018] In another embodiment, the second thermal conductivity enhancer is aluminum nitride.
[0019] In another embodiment, the second thermal conductivity enhancer is present in a first average particle size ranging from 0.5 μm to less than 2 μm, a second average particle size ranging from 2 μm to less than 10 μm, and a third average particle size ranging from 10 μm to about 30 μm.
[0020] In another embodiment, the second thermal conductivity enhancer having a first average particle size is present in an amount of about 5 wt % to about 25 wt % based on the total weight of the composition, the second thermal conductivity enhancer having a second average particle size is present in an amount of about 3 wt % to about 10 wt % based on the total weight of the composition, and the second thermal conductivity filler having a third average particle size is present in an amount of about 5 wt % to about 25 wt % based on the total weight of the composition.
[0021] In yet another embodiment, the third thermal conductivity enhancer is present in an amount from about 1 wt % to about 10 wt %, based on the total weight of the composition.
[0022] In another embodiment, the third thermal conductivity enhancer is zinc oxide having a particle size ranging from 0.01 to less than 0.5 μm.
[0023] In another aspect, provided is a device comprising a first substrate, a second substrate, and a thermal interface material bridging an interfacial gap between the first substrate and the second substrate, the interface material comprising the one-component thermally conductive gel composition of any of the previous embodiments.
[0024] In another aspect, the present invention provides a heat dissipating material comprising the composition of the present invention.
[0025] In another aspect, the present invention provides a method of dissipating heat from a substrate, the method comprising contacting the substrate with a composition of the present invention.
[0026] In yet another aspect, the present invention provides a method of making a treated substrate comprising applying a composition of the present invention to a surface of a substrate.
[0027] In a further aspect, the present invention provides a device comprising a treated substrate, wherein the treated substrate comprises a composition of the present invention. [Brief description of the drawings]
[0028] The following description and drawings disclose various exemplary aspects. Some improvements and novel aspects may be explicitly identified, while others may be apparent from the description and drawings. [Figure 1] FIG. 1 is a photograph showing the vertical stability data obtained for the composition of Example 13. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Reference will now be made to exemplary embodiments, examples of which are illustrated in the accompanying drawings. It should be understood that other embodiments may be used and that structural and functional changes may be made. Furthermore, features of the various embodiments may be combined or substituted. Thus, the following description is presented by way of example only and is not intended to limit in any way the various alternatives and modifications that may be made to the illustrated embodiments. In this disclosure, numerous specific details are provided to provide a thorough understanding of the subject disclosure. It should be understood that aspects of the present disclosure may be implemented using other embodiments that do not necessarily include all aspects set forth herein, and so forth.
[0030] As used herein, the words "example" and "exemplary" mean an example or illustration. The words "example" or "exemplary" do not indicate a primary or preferred aspect or embodiment. The word "or" is intended to be inclusive rather than exclusive, unless the context suggests otherwise. As an example, the phrase "A uses B or C" includes any inclusive permutation (e.g., A uses B, A uses C, or A uses both B and C). As a separate matter, the articles "a" and "an" are generally intended to mean "one or more," unless the context suggests otherwise.
[0031] As used herein, the term "thermal conductivity enhancer" refers to a solid compound or mixture of compounds that enhances the thermal conductivity of a composition. Examples of thermal conductivity enhancers include, but are not limited to, solid inorganic compounds such as boron nitride, aluminum nitride, aluminum oxide, zinc oxide, aluminum metal, silicon carbide, carbon-based fillers such as graphite and diamond, metal fillers such as aluminum, silver, or mixtures thereof.
[0032] As used herein, the term "precured gel" or "crosslinked silicone gel" refers to a polymeric system extended with a fluid, which may include a continuous polymeric phase or network, which may be chemically or physically crosslinked, for example, by ionic or covalent bonds, and oils, such as silicone or other oils, plasticizers, unreacted monomers, or other fluid extenders that fill the interstices of the network by swelling or otherwise. The crosslink density and extender ratio of such a network can be controlled to adjust the elastic modulus, i.e., softness, and other properties of the gel. The term "precured gel" should also be understood to include materials that may be broadly classified as pseudogels or gel-like objects, which have a "loose" crosslinked network formed by relatively long crosslinked chains, but which otherwise have similar viscoelastic properties to gels, for example, by not having a fluid extender.
[0033] The term "monovalent hydrocarbon" refers to any hydrocarbon group from which one or more hydrogen atoms have been removed, and includes alkyl, alkenyl, alkynyl, cyclic alkyl, cyclic alkenyl, cyclic alkynyl, aryl, aralkyl, and arenyl, and may contain heteroatoms.
[0034] The term "alkyl" refers to any monovalent saturated linear, branched, or cyclic hydrocarbon group; the term "alkenyl" refers to any monovalent linear, branched, or cyclic hydrocarbon group containing one or more carbon-carbon double bonds, where the point of attachment of the group may be at the carbon-carbon double bond or elsewhere therein; and the term "alkynyl" refers to any monovalent linear, branched, or cyclic hydrocarbon group containing one or more carbon-carbon triple bonds and optionally one or more carbon-carbon double bonds, where the point of attachment of the group may be at the carbon-carbon triple bond, the carbon-carbon double bond, or elsewhere therein. Examples of alkyl include methyl, ethyl, propyl, and isobutyl. Examples of alkenyl include vinyl, propenyl, allyl, methallyl, ethylidenylnorbornane, ethylidenenorbornyl, ethylidenylnorbornene, and ethylidenenorbornenyl. Examples of alkynyl include acetylenyl, propargyl, and methylacetylenyl.
[0035] The terms "cyclic alkyl," "cyclic alkenyl," and "cyclic alkynyl" include bicyclic, tricyclic, and higher polycyclic structures, as well as those cyclic structures which are further substituted with alkyl, alkenyl, and / or alkynyl groups. Representative examples include norbornyl, norbornenyl, ethylnorbornyl, ethylnorbornenyl, cyclohexyl, ethylcyclohexyl, ethylcyclohexenyl, cyclohexylcyclohexyl, and cyclododecatrienyl.
[0036] The term "aryl" refers to any monovalent aromatic hydrocarbon radical; the term "aralkyl" refers to any alkyl group (as defined herein) in which one or more hydrogen atoms are replaced by an equal number of identical and / or different aryl (as defined herein) groups; and the term "allenyl" refers to any aryl group (as defined herein) in which one or more hydrogen atoms are replaced by an equal number of identical and / or different alkyl groups (as defined herein). Examples of aryl include phenyl and naphthalenyl. Examples of aralkyl include benzyl and phenethyl. Examples of allenyl include tolyl and xylyl.
[0037] The present disclosure provides one-part grease compositions, reworkable pre-cure thermally conductive gel compositions and two-part post-cure compositions consisting of crosslinked silicone gels, alkenyl-functionalized diorganopolysiloxane fluids, hydrogen-functionalized organopolysiloxanes, alkoxy-functionalized surface wetting agents (dispersants) or hydrolyzable organopolysiloxanes, thermally conductive fillers, additives and pigments. Ultra-high thermal conductivity was achieved by using dispersants and organo-functionalized silicone fluids along with diamond and other thermally conductive fillers. Although these thermally conductive compositions consisted of hard fillers such as diamond and AlN fillers, they showed very stable discharge rates over time and outstanding thermal stability at very high temperatures (150°C) for over 1000 hours based on the optimization of the fillers and filler ratios as well as the optimization of the compositions using organo-functionalized silicone fluids in combination with dispersants.
[0038] The one-component precured thermally conductive gel composition achieved a thermal conductivity of more than 14 W / mK along with an extrusion rate of more than 14 g per minute, and the hardness (Shore E) was within 10 at 150°C even after aging for 1000 hours, demonstrating stable extrusion properties.
[0039] A two-component, post-cured (addition curable) thermally conductive composition achieved a thermal conductivity of over 17 W / mK with a delivery rate of over 14 g / min, exhibited less hardness increase at temperatures as high as 150°C, and showed a stable delivery rate after aging.
[0040] The one-component grease composition also comprises additives. The additives used in the present disclosure may be selected from one of the following: pigments, lubricants, viscosity modifiers, heat stabilizers, light stabilizers, antioxidants, flame retardants, inhibitors, adhesion promoters, or a combination of two or more thereof.
[0041] Thermal conductivities exceeding 12 W / mK have been achieved with one-component grease compositions along with delivery rates exceeding 19 g / min.
[0042] The combination of fillers is optimized to arrive at the best combination that can provide a high TC and high ejection composition. Thus, it should be noted that any two or three or more fillers can be combined to obtain a composition, but such an approach is rarely successful and results in powder compositions or low TC compositions. Only after experimental design and optimization can the optimal filler combination be obtained that improves the filler loading, thus providing high thermal conductivity while maintaining paste-like rheological, viscosity and flow properties. The combination of fillers can be described as consisting of three or more fillers - (CI) being the smallest fillers with a D50 of 0.01 to less than 0.5 μm, which can be composed of alumina, ZnO, SiC, diamond, BN and / or aluminum nitride fillers or combinations thereof - these fillers, despite their large surface area, improve the overall TC by providing multiple contacts between filler-polymer-dispersant in conjunction with filler-filler and filler-substrate contacts. They can also provide the desired lubrication and thixotropic effects for the composition. The next fillers (C-II) are intermediate size fillers from 0.5 to 30 μm, which provide improved contact and gap filling between larger fillers, and these fillers consist of alumina, diamond, BN or aluminum nitride powders or combinations thereof. The third filler (C-III) is the largest filler type (>60 to 200 μm), which provides the largest crystalline domain size and provides high thermal conductive paths, i.e., improved thermal conductivity. The largest fillers utilize materials with inherently high TC, such as BN, cubic BN, SiC, diamond and AlN, which improve the overall conductivity of the composition. After careful experimental studies, excellent thermal conductivity (>12 W / mK), throughput (>12 g / min), electrical insulation (volume resistivity >1×10 10In order to achieve a thermally conductive composition having a low viscosity (Ω·cm), flexibility and moldability, and which is easily manufacturable at low cost, specific fillers and combinations of fillers are demonstrated herein for use as thermally conductive fillers, and the present invention has been completed.
[0043] Herein, optimization of the organic functionalized silicone fluids (organosilicone hydrides, vinyl organosilicones, pre-cured silicone gels) along with optimization of fillers (single crystal diamond in combination with other fillers) and optimization of dispersants have been performed to achieve ultra-high thermal conductivity along with good and consistent discharge and good thermal stability.
[0044] The present disclosure may specify a number of different ranges for one or more components in the composition. It will be understood that the numerical values of each range may be combined to form new unspecified ranges.
[0045] In one embodiment, (A) an organopolysiloxane, (i) an alkenyl-functionalized diorganopolysiloxane of formula (Ia) M 1 a M 2 b D 1 c D 2 d T 1 e T 2 f Q g (Ia) [In the formula, M 1 =R 1 R 2 R 3 SiO 1 / 2 M 2 =R 4 R 5 R 6 SiO 1 / 2 D 1 =R 7 R 8SiO 2 / 2 D 2 =R 9 R 10 SiO 2 / 2 T 1 =R 11 SiO 3 / 2 T 2 =R 12 SiO 3 / 2 Q = SiO 4 / 2 where R 2 , R 3 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 12 are each independently selected from monovalent aliphatic, aromatic and fluorohydrocarbon groups or alkoxy groups having from 1 to 60 carbon atoms; R 1 , R 7 , R 11 are each independently selected from monovalent aliphatic, aromatic or fluorohydrocarbon radicals having from 1 to 60 carbon atoms and containing at least one terminal olefinic bond; The subscripts a, b, c, d, e, f, and g are 0 or positive integers, subject to the restrictions that 1≦a+b+c+d+e+f+g≦6000 and a+c+e≧1. and (ii) a hydrogen-functionalized organopolysiloxane of formula (Ib) M 1 a′ M 2 b′ D 1 c′ D 2 d′ T 1 e′ T 2 f′ Q g′ (1b) [In the formula, M 1 =R 13 R 14 R 15SiO 1 / 2 M 2 =R 16 R 17 R 18 SiO 1 / 2 D 1 =R 19 R 20 SiO 2 / 2 D 2 =R 21 R 22 SiO 2 / 2 T 1 =R 23 SiO 3 / 2 T 2 =R 24 SiO 3 / 2 Q = SiO 4 / 2 where R 14 , R 15 , R 16 , R 17 , R 18 , R 20 , R 21 , R 22 , R 24 is a monovalent aliphatic, aromatic or fluorohydrocarbon radical having 1 to 60 carbon atoms; R 13 , R 19 , R 23 is hydrogen, The subscripts a′, b′, c′, d′, e′, f′, and g′ are zero or positive integers, subject to the restrictions that 1≦a′+b′+c′+d′+e′+f′+g′≦6000 and a′+c′+e′≧1. However, when a′+c′+e′=1, a+c+e>1, and when a+c+e=1, a′+c′+e′>1 are also included. or an organopolysiloxane comprising a crosslinked product of (i) and (ii); (B) A composition is provided that includes a first thermal conductivity enhancer having a particle size in the range of 60 to about 200 μm, a second thermal conductivity enhancer having a particle size in the range of 0.5 to about 30 μm, and a third thermal conductivity enhancer having a particle size in the range of 0.01 to less than about 0.5 μm. Component (i) is an organopolysiloxane represented by formula (Ia) and has at least two alkenyl groups bonded to silicon atoms in each molecule. Component (i) may have a viscosity at 25°C in the range of 0.01 to 10 Pa·s, preferably 0.06 to 1 Pa·s. If the viscosity at 25°C is less than 0.01 Pa·s, the storage stability of the composition deteriorates, and if it exceeds 10 Pa·s, flowability cannot be ensured. The viscosities mentioned above and elsewhere in this application are values measured using a Brookfield rotational viscometer. Such organopolysiloxane is not particularly limited as long as it satisfies the above viscosity and alkenyl group content, and known organopolysiloxanes can be used. Examples of the molecular structure of the organopolysiloxane include linear, branched, partially branched linear, and dendrimer. The molecular structure is preferably linear or partially branched linear. The (i) component may be a single polymer having such a structure, a copolymer having such a structure, or a mixture of two or more organopolysiloxanes having different viscosities. Furthermore, component (i) may be used in combination with a monoalkenyl-terminated organopolysiloxane having one alkenyl group bonded to a silicon atom per molecule. The viscosity of this organopolysiloxane at 25°C may be in the range of 0.001 to 1 Pa·s, and preferably 0.006 to 0.1 Pa·s. By using this polyorganosiloxane in combination with component (i), i.e., an organopolysiloxane having at least two alkenyl groups bonded to a silicon atom per molecule, the flowability is improved, and in the case of a cured product, the low hardness required for a thermal interface material is easily obtained. Component (ii) is an organohydrogenpolysiloxane represented by formula (1b) and has a hydrogen atom directly bonded to a silicon atom. That is, it is an organohydrogenpolysiloxane having at least two hydrogen atoms (hydrosilyl groups) directly bonded to silicon atoms in one molecule, and acts as a crosslinking agent for component (i). The hydrosilyl groups in component (ii) and the alkenyl groups in component (i) are added by a hydrosilylation reaction promoted by a platinum group metal curing catalyst described later, to give a three-dimensional network structure having a crosslinked structure. If the number of hydrosilyl groups in component (ii) is less than two, curing is not achieved. The amount of component (ii) added is an amount in which the hydrosilyl group of component (ii) is 0.1 to 5.0 moles per mole of the alkenyl group of component (i), that is, an amount in which the number of moles of hydrogen atoms directly bonded to silicon atoms is 0.1 to 5.0 times the number of moles of the alkenyl group of component (i), preferably an amount of 0.2 to 2.0 moles, more preferably an amount of 0.3 to 1.0 moles. If the amount of hydrosilyl group of component (ii) is less than 0.1 mole per mole of the alkenyl group of component (i), curing may not be achieved or the strength of the cured product may be insufficient and it may not be possible to handle it as a molded product. If the amount exceeds 5.0 moles, the flexibility of the cured product is lost and the cured product becomes brittle.
[0046] In one embodiment, the composition further comprises a dispersant represented by formula (II): [ka] [In the formula, R 25 is a group having an alkoxysilyl group having 1 to 4 carbon atoms, R 26 is a linear organosiloxy group (III), [ka] [In the formula, each R 28are independently monovalent hydrocarbon radicals having 1 to 12 carbon atoms, L is selected from monovalent hydrocarbon radicals having 1 to 6 carbon atoms and alkoxysilyl radicals having 1 to 4 carbon atoms, and k is an integer from 10 to 500. Each X is independently a divalent hydrocarbon group having from 2 to 10 carbon atoms; each of h and i is independently an integer of 1 or greater; j is an integer equal to or greater than 0; h+i+j is an integer equal to or greater than 4, Each R 27 are independently selected from hydrogen and monovalent hydrocarbon radicals having 1 to 6 carbon atoms; or [ka] [In the formula, R 29 represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group, and each R 30 each independently represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group; R 31 and R 32 each represents the same or different unsubstituted or substituted monovalent hydrocarbon group, and each R 33 each independently represents a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group; 34 each independently represents an unsubstituted or substituted alkyl group, alkoxyalkyl group, alkenyl group, or acyl group, and n represents an integer of 2 to 20. The dispersant includes a dispersant represented by:
[0047] In another embodiment, the dispersant comprises two or more hydrolyzable organopolysiloxane compounds of formula (II).
[0048] In yet another embodiment, the dispersant comprises a first hydrolyzable organopolysiloxane represented by formula (III) and having a value of k ranging from 10 to 50, and a second hydrolyzable organopolysiloxane represented by formula (III) and having a value of k ranging from 100 to 500.
[0049] In one embodiment, the organopolysiloxane has an H / Vi ratio greater than 0.4.
[0050] In yet another embodiment, the composition comprises a first thermal conductivity enhancer in an amount from about 15 wt % to about 50 wt %, based on the total weight of the composition.
[0051] In another embodiment, the first thermal conductivity enhancer is diamond.
[0052] In another embodiment, the diamond has a surface oxygen content of greater than 10%.
[0053] In another embodiment, the composition comprises a second thermal conductivity enhancer in an amount from about 20 wt % to about 50 wt %, based on the total weight of the composition.
[0054] In another embodiment, the second thermal conductivity enhancer is aluminum nitride.
[0055] In another embodiment, the second thermal conductivity enhancer is present in a first average particle size ranging from 0.5 μm to less than 2 μm, a second average particle size ranging from 2 μm to less than 10 μm, and a third average particle size ranging from 10 μm to about 30 μm.
[0056] In another embodiment, the second thermal conductivity enhancer having a first average particle size is present in an amount of about 5 wt % to about 25 wt % based on the total weight of the composition, the second thermal conductivity enhancer having a second average particle size is present in an amount of about 3 wt % to about 10 wt % based on the total weight of the composition, and the second thermal conductivity enhancer having a third average particle size is present in an amount of about 5 wt % to about 25 wt % based on the total weight of the composition.
[0057] In yet another embodiment, the third thermal conductivity enhancer is present in an amount from about 1 wt % to about 10 wt %, based on the total weight of the composition.
[0058] In another embodiment, the third thermal conductivity enhancer is zinc oxide having a particle size in the range of 0.01 to 0.5 μm.
[0059] In another aspect, there is provided a device comprising a first substrate, a second substrate, and a thermal interface material bridging an interfacial gap between the first substrate and the second substrate, the interface material comprising the one-component thermally conductive gel composition of any of the previous embodiments.
[0060] In another aspect, the present invention provides a heat dissipating material comprising the composition of the present invention.
[0061] In another aspect, the present invention provides a method of dissipating heat from a substrate, comprising contacting the substrate with a composition of the present invention.
[0062] In yet another aspect, the present invention provides a method of making a treated substrate comprising applying a composition of the present invention to a surface of a substrate.
[0063] In a further aspect, the present invention provides a device comprising a treated substrate, wherein the treated substrate comprises a composition of the present invention.
[0064] It will be understood that the thermal conductivity enhancer may include a mixture of compounds of a single type, and that the mixture may include compounds of different average particle sizes. In one embodiment, the thermal conductivity enhancer includes aluminum nitride, boron nitride, SiC, and aluminum oxide.
[0065] The particle size of the thermal conductivity enhancer may be selected as desired for a particular purpose or intended use. It will be understood that the composition may include a combination of thermal conductivity enhancers with different average particle sizes. Such combinations may be selected as desired for a particular purpose or intended use. In one embodiment, the composition includes a first thermal conductivity enhancer having an average particle size of about 60 μm to about 200 μm, a second thermal conductivity enhancer having an average particle size of about 0.5 μm to about 30 μm, and optionally a third thermal conductivity enhancer having an average particle size of about 0.01 μm to less than about 0.5 μm. The first, second, and third thermal conductivity enhancers may be the same or different from each other in terms of the chemical makeup of the filler. The particle size may be determined by any suitable method. The average particle size is often provided or reported by the material supplier. The average particle size may be determined by measuring the particle size distribution by laser diffraction and scattering according to JIS R1629. In this study, the volume-based median diameter (D50) obtained by measurement was used as the average particle size.
[0066] The filler(s) may be present in an amount of about 80% to about 99% by weight, about 82% to about 96% by weight, or about 85% to about 95% by weight, based on the total weight of the composition.
[0067] The crosslinked silicone gel may also be referred to herein as a pre-cured gel or polymer gel. The crosslinked silicone gel is made by reacting an alkenyl-functionalized diorganopolysiloxane with a hydrogen-functionalized organopolysiloxane. This reaction may be carried out by hydrosilylation reaction conditions using a suitable catalyst. A common hydrosilylation catalyst is a platinum-based catalyst (such as, but not limited to, Karstedt's catalyst). In one embodiment, the pre-cured gel may be made by reacting a linear vinyl-end-capped polysiloxane with a pendant poly(hydrosiloxane) or poly(methylhydrosiloxane) copolymer (crosslinker) or a crosslinked MT or MQ resin containing Si-H reactive groups by a Pt-catalyzed hydrosilylation reaction. Similar gel networks can also be achieved by reacting pendant vinyl silicone polymers with end-capped hydrosiloxyl poly(hydrosiloxane) or poly(methylhydrosiloxane) copolymers or crosslinked MT or MQ resins containing Si-H reactive groups via a Pt-catalyzed hydrosilylation route. The effective Si-H / Si-alkenyl molar ratio [r] reacted to form Si-C bonds must satisfy r≦0.3. The final "gel rheology" must satisfy the following conditions: a) 0.2≦G′≦1000(Pa) b) 0.1≦G″ / G′≦10 Here, the term G' represents the "storage shear modulus" of the final pre-cured gel composition used in the thermal interface material composition, measured at T=25°C under an oscillating frequency of 1 Hz or 6.28 rad / s by a stress or strain controlled rheometer, and the term G" represents the "loss shear modulus" of the final pre-cured gel composition used in the thermal interface material composition, measured at T=25°C under an oscillating frequency of 1 Hz or 6.28 rad / s by a stress or strain controlled rheometer. G" and G' are measured together in their respective viscoelastic regions.
[0068] The following examples are intended to illustrate aspects and embodiments of the present technology. All parts and percentages are by weight and all temperatures are in degrees Celsius unless expressly stated otherwise. All patents, other publications and U.S. patent applications referenced in this application are hereby incorporated by reference in their entirety.
[0069] Working Example
[0070] Steady shear viscosity and thixotropy were determined using a TA Instruments rheometer (DHR-3) using parallel plate geometry (measurement geometry gap 300 μm).
[0071] Hardness test: The hardness of the gel was measured using an ASTM D2240 type durometer (Shore E) and a penetrometer ASTM D-217 (Penetration range: 0 to 400 Pen to 40 mm; Penetration time: 5 seconds).
[0072] The pre-cured (one-part) and post-cured (two-part) compositions were hardness tested using an ASTM D2240 type durometer (Shore E).
[0073] The bulk thermal conductivity of the thermally conductive compositions was measured at 22° C. using a hot disk apparatus, and the thermal resistance and thermal conductivity were measured using ASTM D5470.
[0074] The sample was filled into a 30 cc syringe with a 2 mm opening, named EFD Optimum, and dispensed at 90 psi using a Nordson EFD automated dispenser. The dispensed volume was measured by measuring the dispensed volume per minute.
[0075] The composition was sandwiched between two Si chips of 10×10×0.5 mm, and a pressure of 1 MPa was applied for 30 seconds, and the bond line thickness (BLT) was determined.
[0076] The volume resistivity was measured by a test method conforming to ASTM D257, and the dielectric strength was measured by a test method conforming to ASTM D149.
[0077] Vertical sliding tests (vertical stability performance) were performed by placing 2 grams of the composition to form a circle between an aluminum / alumina Q panel and a glass plate of dimensions 5 cm x 5 cm, using spacers of 0.5 mm, 1 mm, and 2 mm. The plates were clamped together with paper clips, placed in a vertical position, and subjected to temperature cycles or shocks (-40 to 150°C).
[0078] The crystallite size was measured by XRD using an X-ray diffractometer with a copper target (Kα radiation) of 1.54 Å wavelength, an accelerating voltage of 40 kV, a tube current of 30 mA, a scan rate of 4° per minute, and a step width of 0.02°.
[0079] The surface oxygen content was measured using an Al Kα source and a vacuum of 2×10 -9 The measurements were performed by XPS using an X-ray photoelectron spectrometer at Torr, hemispherical analyzer, dwell time of 0.7 seconds, energy step of 1 eV, and HR scan of 0.1 eV.
[0080] The pre-cured gel compositions were made in a Thinky mixer. First, specific amounts of dispersant, vinyl PDMS fluid and gel were weighed into a plastic container and mixed at 2000 rpm for 30 seconds. Fillers of various particle sizes were added to this mixture in stages and all materials were mixed using the Thinky mixer at 2000 rpm for 30 seconds at each stage. After mixing for 30 seconds at each stage, the composition was mixed by hand for 2 minutes using a broad blade spatula. Finally, it was mixed 1 to 2 times at 2000 rpm for 30 seconds to obtain a homogenous paste.
[0081] The two-component curable composition was prepared in the same manner as the precured gel composition. Components A and B were prepared separately, mixed in equal amounts, and cured at 70°C for 1 hour.
[0082] Thermally conductive grease type compositions were prepared according to Examples 1 to 12 using irregular polycrystalline diamond, single crystal diamond fillers and other thermally conductive fillers.
[0083] Two-part addition curable compositions were prepared according to Examples 13-17.
[0084] Thermally conductive pre-cured gel compositions were prepared according to Examples 18-22.
[0085] Tables 1 and 2 show the properties of the thermally conductive grease compositions.
[0086] Table 3 shows the properties of the two-part addition curable compositions.
[0087] Table 4 shows the properties of the thermally conductive precured gel compositions.
[0088] The divinyl-terminated organopolysiloxane (A-1a) has a viscosity of 0.1 Pa s and is represented by the following formula: [ka] wherein each X is vinyl and n is 42. The divinyl-terminated organopolysiloxane (A-1b) has a viscosity of 0.03 Pa s and is represented by the following formula: [ka] wherein each X is vinyl and n is 20.
[0089] The monovinyl-terminated organopolysiloxane (A-2a) has a viscosity of 0.02 Pa s and is represented by the following formula: [ka] In this formula, X is vinyl and m is 30. The monovinyl-terminated organopolysiloxane (A-2b) has a viscosity of 0.01 Pa·s and is represented by the following formula: [ka] In this formula, X is vinyl and m is 20.
[0090] The crosslinker organohydrogenpolysiloxane (B-1) has a viscosity range of 0.01 to 0.1 Pa·s with a Si—H content of 0.05 to 0.5 wt.%, and the compound of the following formula having a viscosity of 0.02 Pa·s was used in the examples: [ka]
[0091] Irregularly shaped polycrystalline diamond was purchased from either HongXiang or Hexanovation.
[0092] Aluminum nitride was purchased from Toyo Aluminum Co., Ltd.
[0093] Nano zinc oxide was obtained from Zochem.
[0094] Irregular polycrystalline diamond (C-1) with a volume average grain size of 0.57 μm, a crystallite size of 306 Å, and a surface oxygen content of 10.9%.
[0095] Irregular polycrystalline diamond (C-2) with a volume average grain size of 5.2 μm, a crystallite size of 428 Å, and a surface oxygen content of 8.1%.
[0096] Irregular polycrystalline diamond (C-3) with a volume average grain size of 83.5 μm and a surface oxygen content of 8.6%
[0097] Irregular polycrystalline diamond (C-4) with a volume average grain size of 89 μm, a crystallite size of 1070 Å, and a surface oxygen content of 6.9%.
[0098] Irregular polycrystalline diamond (C-5) with a volume average grain size of 115 μm, a crystallite size of 1097 Å, and a surface oxygen content of 10.1%.
[0099] Single crystal diamond (C-6) with a volume average grain size of 165 μm, a crystallite size of 1206 Å, and a surface oxygen content of 13.5%.
[0100] Single crystal diamond (C-7) with a volume average diameter of 125 μm
[0101] Single crystal diamond (C-7a) with a volume average grain size of 107 μm, a crystallite size of 905 Å, and a surface oxygen content of 16.7%.
[0102] Alumina nitride with volume average particle diameters of 1.2, 5, 20 and 70 μm (C-8a, C-8b, C-8c and C-8d, respectively)
[0103] Nano zinc oxide (C-9) with a volume average particle size of 0.16 μm
[0104] (D-1) is a hydrolyzable organopolysiloxane (II-i) represented by the compound of the following formula: [ka]
[0105] (D-2) is a hydrolyzable polyorganosiloxane represented by the compound of formula (II-ii). [ka]
[0106] E-1 is an additive in the composition.
[0107] Example 1: Polysiloxanes A-1a (0.06 g) and A-2a (0.9 g), hydrolyzable polysiloxane D-1 (0.61 g) were weighed into a plastic container and mixed using a Thinky mixer at 2000 rpm for 30 seconds. To this mixture, thermally conductive fillers C-4 (16 g), C-8a (8 g), and C-8c (8 g) were added stepwise, and all materials were mixed using a Thinky mixer at 2000 rpm for 30 seconds each step. After each 30 second mixing period, the composition was mixed by hand for 2 minutes using a broad blade spatula. The mixture was further mixed in the Thinky mixer at 2000 rpm for 30 seconds. After mixing, the composition was degassed at room temperature to remove any air trapped inside. The total weight of the composition was 33.6 g.
[0108] Example 2 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.08 g), hydrolyzable polysiloxane D-1 (2.08 g), thermally conductive fillers C-4 (15.6 g), C-8a (13.78 g), and C-8c (11 g). The total weight of the composition was 42.54 g.
[0109] Example 3 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.08 g), hydrolyzable polysiloxane D-1 (1.77 g), thermally conductive filler C-4 (14.76 g), C-8a (9.85 g), and C-8c (15.7 g). The total weight of the composition was 42.16 g.
[0110] Example 4 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.05 g), A-2a (1.13 g), hydrolyzable polysiloxane D-1 (0.75 g) with thermally conductive fillers C-1 (3.68 g), C-2 (2.45 g), C-8a (7.46 g), and C-8d (18.05 g). The total weight of the composition was 33.56 g.
[0111] Example 5 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.06 g), A-2a (0.78 g), hydrolyzable polysiloxane D-1 (0.43 g), thermally conductive filler C-2 (3.8 g), C-8a (10.5 g), C-8d (21.07 g), and additive KBM3103 (decyltrimethoxysilane) E-1 (0.77 g). The total weight of the composition was 37.41 g.
[0112] Example 6 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.08 g), A-2a (0.94 g), hydrolyzable polysiloxane D-1 (0.63 g) with thermally conductive fillers C-5 (16 g), C-8a (8.0 g), and C-8c (8.0 g). The total weight of the composition was 33.68 g.
[0113] Example 7 was prepared by mixing polysiloxane A-1a (0.06 g), A-2a (0.92 g), hydrolyzable polysiloxane D-1 (0.62 g), thermally conductive fillers C-6 (16 g), C-8a (8.0 g), and C-8c (8.0 g) in the same manner as in Example 1. The total weight of the composition was 33.72 g.
[0114] Example 8 was prepared by mixing polysiloxane A-1a (0.66 g), A-2a (0.60 g), hydrolyzable polysiloxane D-1 (0.51 g) with thermally conductive fillers C-3 (22.5 g), C-8a (7.51 g), C-8b (5.0 g), C-8c (10.38 g), and C-9 (2.89 g) in the same manner as in Example 1. The total weight of the composition was 50.04 g.
[0115] Example 9 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.06 g), A-2a (0.99 g), hydrolyzable polysiloxane D-1 (0.61 g), thermally conductive filler C-6 (18.02 g), C-8a (7.5 g), C-8b (3.32 g), C-8c (6.33 g), C-9 (1.51 g), and additive KBM3103 (decyltrimethoxysilane) E-1 (0.13 g). The total weight of the composition was 38.46 g.
[0116] Example 10 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.15 g), A-2a (2.7 g), hydrolyzable polysiloxane D-1 (1.8 g) with thermally conductive fillers C-4 (47.7 g), C-8a (23.8 g), and C-8c (23.8 g). The total weight of the composition was 100 g.
[0117] Example 11 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (0.15 g), A-2a (2.7 g), hydrolyzable polysiloxane D-1 (1.8 g) with thermally conductive fillers C-6 (47.7 g), C-8a (23.8 g), and C-8c (23.8 g). The total weight of the composition was 100 g.
[0118] Example 12 was prepared in the same manner as in Example 1 by mixing polysiloxane A-1a (1.6 g), A-2a (1.8 g), hydrolyzable polysiloxane D-1 (1.2 g) with thermally conductive fillers C-2 (3.0 g), C-6 (47.7 g), C-8a (17.9 g), C-8c (20.9 g), and C-9 (6.0 g). The total weight of the composition was 100 g.
[0119] Example 13
[0120] Component A: Polysiloxanes A-1a (1.00 g) and A-2a (1.21 g), hydrolyzable polysiloxane D-1 (1.0 g), platinum catalyst G-1 (18 wt% solution of platinum dimer complex with 2 wt% platinum amount in monovinyl-terminated organopolysiloxane (viscosity 0.02 Pa·s)) (0.286 g) were weighed into a plastic container and mixed for 30 seconds at 2000 rpm using a Thinky mixer. Thermally conductive fillers C-6 (45.0 g), C-8a (15.0 g), C-8b (10.0 g), C-8c (20.75 g), and C-9 (5.75 g) were added stepwise to this mixture, and all materials were mixed with the Thinky mixer at 2000 rpm for 30 seconds in each step. After each mixing for 30 seconds, the composition was mixed by hand for 2 minutes using a broad blade spatula. The composition was further mixed in a Thinky mixer at 2000 rpm for 30 seconds. After mixing, the composition was degassed at room temperature to remove any trapped air. The total weight of the composition was 100 g.
[0121] Component B: Polysiloxanes A-1a (1.00 g) and A-2a (1.18 g), hydrolyzable polysiloxane D-1 (1.0 g), crosslinker B-1 (hydrogen-functionalized organopolysiloxane) (0.12 g), and reaction inhibitor F-1, a 1.5 wt% solution (0.2 g) of bis-{(1,1-dimethyl-2-propynyl)oxy}dimethyl-silane in crosslinker organohydrogenpolysiloxane (viscosity 0.02 Pa·s), were weighed into a plastic container and mixed for 30 seconds at 2000 rpm using a Thinky mixer. To this mixture, thermally conductive fillers C-6 (45.0 g), C-8a (15.0 g), C-8b (10.0 g), C-8c (20.75 g), and C-9 (5.75 g) were added stepwise and all materials were mixed in a Thinky mixer at 2000 rpm for 30 seconds in each step. After each 30 second mixing, the composition was mixed by hand for 2 minutes using a broad blade spatula. The mixture was further mixed in a Thinky mixer at 2000 rpm for 30 seconds. After mixing, the composition was degassed at room temperature to remove any air trapped inside. The total weight of the composition was 100 g.
[0122] Example 14 was prepared similarly to Example 13 as follows.
[0123] Component A: Polysiloxane A-1a (1.30 g) and A-2a (1.87 g), hydrolyzable polysiloxane D-1 (1.0 g), Pt catalyst G-1 (18 wt% solution of platinum dimer complex with 2 wt% platinum amount in monovinyl-terminated organopolysiloxane (viscosity 0.02 Pa·s)) (0.285 g) were mixed with thermally conductive fillers C-6 (48.5 g), C-8a (15.0 g), C-8b (5.0 g), C-8c (21.03 g), and C-9 (6.0 g). The total weight of the composition was 100 g.
[0124] B component: Polysiloxane A-1a (1.30 g) and A-2a (1.75 g), hydrolyzable polysiloxane D-1 (1.0 g), crosslinker B-1 (hydrogen-functionalized organopolysiloxane) (0.13 g), reaction inhibitor F-1, 1.5 wt% solution (0.283 g) of bis-{(1,1-dimethyl-2-propynyl)oxy}dimethyl-silane in crosslinker organohydrogenpolysiloxane (viscosity 0.02 Pa·s) was mixed with thermally conductive filler C-6 (48.5 g), C-8a (15.0 g), C-8b (5.0 g), C-8c (21.03 g), and C-9 (6.0 g). The total weight of the composition was 100 g.
[0125] Example 15 was prepared similarly to Example 13 as follows.
[0126] Component A: Polysiloxane A-1b (0.98 g) and A-2b (0.32 g), hydrolyzable polysiloxane D-2 (0.37 g), Pt catalyst G-1 (18 wt% solution of platinum dimer complex with 2 wt% platinum amount in monovinyl-terminated organopolysiloxane (viscosity 0.01 Pa·s)) (0.18 g) were mixed with thermally conductive filler C-7 (24.09 g), C-8a (9.36 g), C-8b (4.16 g), and C-8c (8.55 g). The total weight of the composition was 48.03 g.
[0127] B component liquid: Polysiloxane A-1b (0.98g) and A-2b (0.1g), hydrolyzable polysiloxane D-2 (0.37g), crosslinker B-1 (hydrogen functionalized organopolysiloxane) (0.22g), reaction inhibitor F-1, 1.5 wt% solution (0.21g) of bis-{(1,1-dimethyl-2-propynyl)oxy}dimethyl-silane in crosslinker organohydrogenpolysiloxane (viscosity 0.02 Pa·s) was mixed with thermally conductive filler C-7 (24.09g), C-8a (9.36g), C-8b (4.16g), and C-8c (8.55g). The total weight of the composition was 48.06g.
[0128] Example 16 was prepared similarly to Example 13 as follows.
[0129] A component liquid: Polysiloxane A-1b (0.98g) and A-2b (0.32g), hydrolyzable polysiloxane D-2 (0.37g), Pt catalyst G-1 (18wt% solution of platinum dimer complex with 2wt% platinum amount in monovinyl-terminated organopolysiloxane (viscosity 0.01 Pa·s)) (0.18g) were mixed with thermally conductive filler C-7 (24.09g), C-8a (9.36g), C-8b (4.16g), C-8c (8.55g), and C-9 (1.94g). The total weight of the composition was 50g.
[0130] B component liquid: Polysiloxane A-1b (0.98g) and A-2b (0.1g), hydrolyzable polysiloxane D-2 (0.37g), crosslinker B-1 (hydrogen functionalized organopolysiloxane) (0.22g), reaction inhibitor F-1, 1.5 wt% solution (0.21g) of bis-{(1,1-dimethyl-2-propynyl)oxy}dimethyl-silane in crosslinker organohydrogenpolysiloxane (viscosity 0.02 Pa·s) was mixed with thermally conductive filler C-7 (24.09g), C-8a (9.36g), C-8b (4.16g), C-8c (8.55g), and C-9 (1.94g). The total weight of the composition was 50g.
[0131] Example 17 was prepared similarly to Example 13 as follows.
[0132] A component liquid: Polysiloxane A-1b (0.98g) and A-2b (0.32g), hydrolyzable polysiloxane D-2 (0.37g), Pt catalyst G-1 (18wt% solution of platinum dimer complex with 2wt% platinum amount in monovinyl-terminated organopolysiloxane (viscosity 0.01 Pa·s)) (0.18g) were mixed with thermally conductive filler C-7 (24.09g), C-8a (9.36g), C-8b (4.16g), C-8c (8.55g), and C-9 (2.91g). The total weight of the composition was 50.97g.
[0133] B component liquid: Polysiloxane A-1b (0.98g) and A-2b (0.1g), hydrolyzable polysiloxane D-2 (0.37g), crosslinker B-1 (hydrogen functionalized organopolysiloxane) (0.22g), reaction inhibitor F-1, 1.5 wt% solution (0.21g) of bis-{(1,1-dimethyl-2-propynyl)oxy}dimethyl-silane in crosslinker organohydrogenpolysiloxane (viscosity 0.02 Pa·s) was mixed with thermally conductive filler C-7 (24.09g), C-8a (9.36g), C-8b (4.16g), C-8c (8.55g), and C-9 (2.91g). The total weight of the composition was 50.97g.
[0134] Synthesis of crosslinked polysiloxane: Vinyl-terminated PDMS (500 g, MW ~ 17280 g / mol, vinyl milliequivalent ~ 0.115) was charged to a double planetary mixer at room temperature along with Pt catalyst (2 wt% Karstedt catalyst, 10 ppm Pt) and inhibitor (Surfynol® 61, 200 ppm) and mixed at 20 rpm for 30 minutes at room temperature. Silicone hydride (55.4 g, MW ~ 40802, hydride milliequivalent ~ 0.1586) was added to the reaction mixture at 50°C and mixing was continued at 20 rpm for an additional hour. With continued mixing at the same speed at 50°C, a vacuum was applied for 60 minutes to remove the reaction inhibitor and form a gel network. The reaction temperature was then increased to 90°C and continued until all the hydride was consumed and a gel was formed.
[0135] Example 18: Polysiloxane A-1a (1.5 g), crosslinked polysiloxane (1.0 g), and hydrolyzable polysiloxane D-1 (1.0 g) were weighed into a plastic container and mixed using a Thinky mixer at 2000 rpm for 30 seconds. To this mixture, thermally conductive fillers C-6 (45.0 g), C-8a (15.0 g), C-8b (10.0 g), C-8c (20.75 g), and C-9 (5.75 g) were added stepwise and all materials were mixed using a Thinky mixer at 2000 rpm for 30 seconds each step. After each 30 second mixing, the composition was mixed by hand for 2 minutes using a broad blade spatula. The mixture was further mixed with the Thinky mixer at 2000 rpm for 30 seconds. After mixing, the composition was degassed at room temperature to remove any air trapped inside. The total weight of the composition was 100 g.
[0136] Example 19 was prepared in the same manner as in Example 18 by mixing polysiloxane A-1a (1.75 g), crosslinked polysiloxane (1.0 g), hydrolyzable polysiloxane D-1 (1.5 g) with thermally conductive fillers C-6 (48.5 g), C-8a (15.0 g), C-8b (5.0 g), C-8c (20.95 g), and C-9 (6.0 g). The total weight of the composition was 100 g.
[0137] Example 20 was prepared in the same manner as in Example 18 by mixing polysiloxane A-1a (1.65 g), crosslinked polysiloxane (1.1 g), hydrolyzable polysiloxane D-1 (1.1 g) with thermally conductive fillers C-6 (45.0 g), C-8a (15.0 g), C-8b (10.0 g), C-8c (20.75 g), and C-9 (5.75 g). The total weight of the composition was 100 g.
[0138] Example 21 was prepared in the same manner as in Example 18 by mixing polysiloxane A-1a (1.75 g), crosslinked polysiloxane (1.0 g), hydrolyzable polysiloxane D-1 (1.5 g) with thermally conductive fillers C-6 (48.5 g), C-8a (15.0 g), C-8b (5.0 g), C-8c (20.95 g), and C-9 (6.0 g). The total weight of the composition was 100 g.
[0139] Example 22 was prepared in the same manner as in Example 18 by mixing polysiloxane A-1a (1.75 g), crosslinked polysiloxane (1.0 g), hydrolyzable polysiloxane D-1 (1.5 g), thermally conductive filler C-6 (48.5 g), C-8a (15.0 g), C-8b (5.0 g), C-8c (20.95 g), C-9 (6.0 g), and antioxidant (2,4,6-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl)mesitylene and didodecyl 3,3'-thiodipropionate) (0.3 g). The total weight of the composition was 100 g.
[0140] Thermally conductive grease-type compositions using irregular polycrystalline diamond fillers and other thermally conductive fillers [Table 1]
[0141] As can be seen from Table 1, the compositions with different loadings of filler, dispersant and polymer resin were optimized by using different particle sizes of filler. In some cases, the compositions were dry and no jettability was obtained. When irregular polycrystalline diamond was used in the compositions, low jettance, low thermal conductivity was observed and the compositions were not stable.
[0142] Single crystal diamond was used in conjunction with other thermally conductive fillers to improve the thermal conductivity, dispensing rate and stability of the thermally conductive composition (Table 2). [Table 2]
[0143] As shown in Table 2, the composition containing the mixture of thermal conductivity enhancer and single crystal diamond exhibited better thermal conductivity and jettability.
[0144] Ultra-high thermal conductivity two-component addition-curing thermally conductive composition [Table 3]
[0145] TIA2101GF is a commercially available two-part silicone composition manufactured by Momentive Performance Materials.
[0146] Two-part, addition-cured thermally conductive compositions with different filler loadings were prepared to achieve very good and stable discharge rates (>20 g / min) and very high thermal conductivity (>20 W / mK) with good thermal stability (Table 3). Part A and Part B were mixed in a 1:1 ratio and cured at 70°C for 1 hour. The H / Vi ratios of the cured samples range from 0.4 to 0.9.
[0147] As can be seen from Table 3, Examples 13, 14, 16 and 17 exhibited thermal conductivity of over 12 W / mK with dispensing rates of over 13 g per minute, and also exhibited less hardness increase at a high temperature of 150° C. and stable discharge rates after aging.
[0148] As shown in FIG. 1, the vertical stability performance under thermal shock (from bottom to top, gaps of 0.5 mm, 1 mm, and 2 mm) after 500 hours under thermal shock (from −40° C. to 150° C.) of Example 13 showed very good vertical stability.
[0149] Highly heat conductive pre-cured gel composition
[0150] [Table 4]
[0151] Pre-cured thermally conductive gel compositions based on the combination of single crystal diamond and other fillers were designed and showed very high thermal conductivity ranging from 14 to 21 W / mK (Table 4). These thermally conductive gel compositions have hard fillers such as AlN and diamond fillers, and in spite of being highly filled thermally conductive compositions, they showed very good thermal stability over ultra-high temperatures. These thermally conductive gel compositions showed much less hardness increase at 150°C. For example, Example 19 showed much less hardness increase (Shore E) at 150°C even up to 1000 hours and showed a stable discharge rate.
[0152] The above description includes the examples of the present specification. It is of course not possible to describe every conceivable combination of elements or methods for purposes of describing the present specification, but one skilled in the art can recognize that many further combinations and permutations of the present specification are possible. Accordingly, the present specification is intended to embrace all such alternatives, modifications, and variations that fall within the spirit and scope of the appended claims. Moreover, to the extent that the term "comprises" is used in either the detailed description or the claims, such term is intended to be inclusive in the same manner as "comprises" is interpreted when the term "comprises" is used as a transitional phrase in the claims.
[0153] The above description identifies various non-limiting embodiments of the thermally conductive gel composition. Modifications will occur to those skilled in the art and those able to make and use the invention. The disclosed embodiments are merely illustrative and are not intended to limit the scope of the invention or the subject matter defined in the claims.
Claims
1. (A) an organopolysiloxane, (i) an alkenyl-functionalized diorganopolysiloxane of formula (Ia) M 1 a M 2 b D 1 c D 2 d T 1 e T 2 f Q g (Ia) [In the formula, M 1 =R 1 R 2 R 3 SiO 1/2 M 2 =R 4 R 5 R 6 SiO 1/2 D 1 =R 7 R 8 SiO 2/2 D 2 =R 9 R 10 SiO 2/2 T 1 =R 11 SiO 3/2 T 2 =R 12 SiO 3/2 Q=SiO 4/2 where R 2 , R 3 , R 4 , R 5 , R 6 , R 8 , R 9 , R 10 , R 12 are each independently selected from monovalent aliphatic, aromatic and fluorohydrocarbon groups or alkoxy groups having 1 to 60 carbon atoms; R 1 , R 7 , R 11 are each independently selected from monovalent aliphatic, aromatic or fluorohydrocarbon radicals having from 1 to 60 carbon atoms and containing at least one terminal olefinic bond; The subscripts a, b, c, d, e, f, and g are 0 or positive integers, subject to the restrictions that 1≦a+b+c+d+e+f+g≦6000 and a+c+e≧1. and (ii) a hydrogen-functionalized organopolysiloxane of formula (Ib) M 1 a′ M 2 b′ D 1 c′ D 2 d′ T 1 e′ T 2 f′ Q g′ (1b) [In the formula, M 1 =R 13 R 14 R 15 SiO 1/2 M 2 =R 16 R 17 R 18 SiO 1/2 D 1 =R 19 R 20 SiO 2/2 D 2 =R 21 R 22 SiO 2/2 T 1 =R 23 SiO 3/2 T 2 =R 24 SiO 3/2 Q=SiO 4/2 where R 14 , R 15 , R 16 , R 17 , R 18 , R 20 , R 21 , R 22 , R 24 is a monovalent aliphatic, aromatic or fluorohydrocarbon radical having 1 to 60 carbon atoms; R 13 , R 19 , R 23 is hydrogen, The subscripts a', b', c', d', e', f' and g' are 0 or positive integers, subject to the restrictions that 1≦a'+b'+c'+d'+e'+f'+g'≦6000 and a'+c'+e'≧1. However, when a'+c'+e'=1, a+c+e>1, and when a+c+e=1, a'+c'+e'>1 are included. or an organopolysiloxane comprising a crosslinked product of (i) and (ii); (B) a composition comprising a first thermal conductivity enhancer having a particle size in the range of 60 to about 200 μm, a second thermal conductivity enhancer having a particle size in the range of 0.5 to about 30 μm, and optionally a third thermal conductivity enhancer having a particle size in the range of 0.01 to less than about 0.5 μm.
2. The composition of claim 1 further comprising a dispersant represented by formula (II). 【Chemistry 14】 [In the formula, R 25 is a group having an alkoxysilyl group having 1 to 4 carbon atoms, R 26 is a linear organosiloxy group (III), 【Chemistry 15】 [In the formula, each R 28 are independently a monovalent hydrocarbon group having 1 to 12 carbon atoms, L is selected from monovalent hydrocarbon groups having 1 to 6 carbon atoms and alkoxysilyl groups having 1 to 4 carbon atoms, and k is an integer from 10 to 500. Each X is independently a divalent hydrocarbon group having from 2 to 10 carbon atoms; each of h and i is independently an integer of 1 or greater; j is 0 or a greater integer; h+i+j is an integer equal to or greater than 4; Each R 27 are independently selected from hydrogen and monovalent hydrocarbon radicals having 1 to 6 carbon atoms, or are represented by formula (IV): 【Chemistry 16】 [In the formula, R 29 represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group, and each R 30 each independently represents an unsubstituted or substituted alkyl group, alkenyl group, or aryl group; R 31 and R 32 each represents the same or different unsubstituted or substituted monovalent hydrocarbon group, and each R 33 each independently represents a hydrogen atom or an unsubstituted or substituted monovalent hydrocarbon group; 34 each independently represents an unsubstituted or substituted alkyl group, alkoxyalkyl group, alkenyl group, or acyl group, and n represents an integer of 2 to 20.
3. The composition of claim 1 wherein the organopolysiloxane has an H / Vi ratio greater than 0.
4.
4. The dispersant is represented by the formula (II) 【Chemistry 17】 The composition according to claim 2, wherein the compound is represented by the formula:
5. 5. The composition of claim 4, wherein the dispersant comprises two or more hydrolyzable organopolysiloxane compounds of formula (II).
6. 5. The composition of claim 4, wherein the dispersant comprises a first hydrolyzable organopolysiloxane represented by formula (II) and having a value of k in the range of 10 to 50, and a second hydrolyzable organopolysiloxane represented by formula (II) and having a value of k in the range of 100 to 500.
7. 7. The composition of claim 1, wherein the composition comprises the first thermal conductivity enhancer in an amount of 15 wt% to 50 wt%, based on the total weight of the composition.
8. The composition of claim 7 , wherein the first thermal conductivity enhancer is diamond.
9. The composition of claim 8, wherein the diamond has a surface oxygen content of greater than 10%.
10. 9. The composition of claim 7 or 8, wherein the composition comprises the second thermal conductivity enhancer in an amount of from 20 wt% to 50 wt%, based on the total weight of the composition.
11. The composition of claim 10 , wherein the second thermal conductivity enhancer is aluminum nitride.
12. 12. The composition of claim 10 or 11, wherein the second thermal conductivity enhancer is present in a first average particle size in the range of 0.5 μm to less than 2 μm, a second average particle size in the range of 2 μm to less than 10 μm, and a third average particle size in the range of 10 μm to 30 μm.
13. 13. The composition of claim 12, wherein the second thermal conductivity enhancer having the first average particle size is present in an amount of 5 wt. % to 25 wt. % based on the total weight of the composition, the second thermal conductivity enhancer having the second average particle size is present in an amount of 3 wt. % to 10 wt. % based on the total weight of the composition, and the second thermal conductivity enhancer having the third average particle size is present in an amount of 5 wt. % to 25 wt. % based on the total weight of the composition.
14. 14. The composition of claim 1, comprising the third thermal conductivity enhancer in an amount of from 1 wt% to 10 wt%, based on the total weight of the composition.
15. 15. The composition of claim 14, wherein the third thermal conductivity enhancer is zinc oxide having a particle size in the range of 0.01 to less than 0.5 μm.
16. 16. A device comprising a first substrate, a second substrate and a thermal interface material filling an interface gap between the first substrate and the second substrate, the interface material comprising the composition of any one of claims 1 to 15.
17. A heat dissipating material comprising the composition of any one of claims 1 to 15.
18. 16. A method of dissipating heat from a substrate, comprising contacting the substrate with the composition of any one of claims 1 to 15.
19. A method of making a treated substrate comprising applying a composition according to any one of claims 1 to 15 to a surface of a substrate.
20. 16. A device comprising a processed substrate, said processed substrate comprising the composition of any one of claims 1 to 15.
Citation Information
Patent Citations
Diamond-based heat-conducting filler and preparation method thereof, composite heat-conducting material and electronic equipment
CN115725273A
Thermally conductive polyorganosiloxane composition
WO2018016564A1
Thermal GEL composition
WO2022187569A1
Cited By
Thermally conductive grease composition
WO2026203926A1